[PP.36.11] "REVERSE" VASCULAR REACTION AFTER BRACHIAL ARTERY OCCLUSION (FMD) IS RELATED TO THE IMPAIRED HEMODYNAMICS IN HYPERTENSIVES. (September 2016) - Stanczyk, A.; Krzesinski, P.; Gielerak, G.; Kurpaska, M.; Uzieblo-Zyczkowska, B.; Piotrowicz, K.; Skrobowski, A.
Abstract : Objective: The assessment of extension of brachial artery after 5-minute occlusion of the proximal arm (FMD, flow-mediated dilatation) is commonly used in endothelial evaluation. FMD is an independent predictor of cardiovascular risk, and may be related with impaired systemic hemodynamics. The assessment of relationship between FMD and selected clinical and hemodynamic parameters in patients with untreated arterial hypertension (AH). Design and method: The study (ClinicalTrials.gov, NCT01996085) involved 133 hypertensives (mean age: 44.9 years). FMD was measured at morning hours with use of linear transducer 12 MHz. The hemodynamic profile was assessed by non-invasive methods (impedance cardiography, applanation tonometry, echocardiography), drawing special attention to: systolic and diastolic blood pressure (SBP, DBP), systemic vascular resistance index (SVRI), total arterial compliance (TAC), stroke and cardiac index (SI, CI), velocity index (VI), acceleration index (ACI), Heather index (HI), augmentation index (AI), central blood pressure (cSBP, cDBP), central pulse pressure (cPP) and left ventricular diastolic (E/A, e') and global longitudinal systolic strain (GLSS). The interquartile analysis in subgroups of FMD: < 0% (Q1), 0–2.28% (Q2), 2.29–6.15% (Q3), > = 6.16% (Q4) was performed. Results: The mean FMD in the total group was 2.84±5.4%. Proper vascular reaction (FMD >7%) was observed only in 26 subjects (20%). There were no differences in FMD with respect to demographic and constitutional data (age, gender, obesity, smoking). The subjects with reactive constriction after brachial artery occlusion (FMD < 0%; "reverse FMD reaction") in comparison to the rest of the group, presented higher peripheral DBP (92.8 ± 7.5 vs. 87.3 ± 9.2[mmHg], p = 0.002), central DBP (93.9 ± 7.8 vs. 88.3 ± 9.4[mmHg], p = 0.002) and SVRI (2371 ± 468 vs. 2242 ± 462[dyn*s*m 2 /cm5], p = 0.049). Moreover, significantly lower indicators of LV systolic (GLSS -17.1 ± 2, 7 vs. -18.4 ± 2.8[%], p = 0.018; VI 44.0 ± 14.4 vs. 49.4 ± 13.6[1/100/s], p = 0.018; ACI 62.5 ± 27.1 vs. 75.5 ± 30.8[1/1000/s2], p = 0.026; HI 11.8 ± 3.6 vs. 13.6 ± 4.2[Ohm*s2], p = 0.024) and diastolic function (E/A 0.97 ± 0.31 vs. 1.11 ± 0.34, p = 0.022; e' 8.77 ± 2.33 vs. 10.0 ± 2.64[cm/s], p = 0.019) were noted in that subgroup. Figure. No caption available. Conclusions: Flow-mediated constriction (reverse FMD reaction) is related to impaired afterload and LV systolic and diastolic dysfunction.